The merchants of cool - Goodman, Barak; Goodman, Rachel Dretzin; Rushkoff, Douglas; 10/20 Productions; WGBH Educational Foundation; WGBH (Television station : Boston, Mass.); PBS Home Video ([Alexandria, Va.] : Distributed by PBS Home Video, 2003)
"Frontline journeys into the world of the marketers of popular culture to teenagers. They spend their days sifting through reams of market research data. They conduct endless surveys and focus groups. They comb the streets, the schools, and the malls, hot on the trail of the 'next big thing' that will snare the attention of their prey, a market segment worth an estimated $300 billion a year. They are the merchants of cool: the creators and sellers of popular culture, who have made teens the hottest consumer demographic in America."--Http://www.pbs.org/wgbh/pages/frontline .
Originally broadcast as a segment of the television program: Frontline.
Correspondent, Douglas Rushkoff.
DVD.
Closed-captioned.
Keywords: Teenage consumers -- United States; Advertising and youth -- United States; Mass media and teenagers -- United States; Marketing -- Moral and ethical aspects -- United States; Marketing -- Social aspects -- United States; Popular culture -- United States; Video recordings for the hearing impaired; Documentary television programs